2014
DOI: 10.1111/jfb.12441
|View full text |Cite
|
Sign up to set email alerts
|

Predictability of food supply, but not ration, increases exploratory behaviour in zebrafish Danio rerio

Abstract: Individual zebrafish Danio rerio were assayed for exploratory tendency in a serial open field test before and after being maintained on one of four diet treatments that differed in ration and in predictability of food delivery. Danio rerio became more exploratory after being maintained on a diet with a predictable delivery schedule. There was no effect of ration. Thus, exploratory behaviour is inducible by environmental influences independent of genetic predisposition or social interactions. These results have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…Chapman et al, (2010) found that Trinidadian guppies, Poecilia reticulata, reared under conditions of unpredictable food supply spent less time in a refuge zone than fish reared with a predictable food supply and similar findings have been reported for juvenile cod, Gadus morhua (Braithwaite and Salvanes, 2005). Opposite results were however observed in zebrafish, Danio rerio (Holley et al, 2014). Here, our first objective was to assess how food predictability was affecting boldness in seabass.…”
Section: Introductionsupporting
confidence: 60%
“…Chapman et al, (2010) found that Trinidadian guppies, Poecilia reticulata, reared under conditions of unpredictable food supply spent less time in a refuge zone than fish reared with a predictable food supply and similar findings have been reported for juvenile cod, Gadus morhua (Braithwaite and Salvanes, 2005). Opposite results were however observed in zebrafish, Danio rerio (Holley et al, 2014). Here, our first objective was to assess how food predictability was affecting boldness in seabass.…”
Section: Introductionsupporting
confidence: 60%
“…For instance, the positive relationship between body size and boldness (an aspect of proactiveness) has been well documented in various species of fish (Brown & Braithwaite, 2004 ; Brown, Jones, & Braithwaite, 2007 ; Harris et al, 2010 ; Meuthen et al, 2019 ). Furthermore, it is also possible that patterns of feeding (e.g., frequency or schedule) rather than diet per se could influence exploration in zebrafish (Holley et al, 2014 ; Le Roy et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the positive relationship between body size and boldness (an aspect of proactiveness) has been well documented in various species of fish (Brown & Braithwaite, 2004;Brown, Jones, & Braithwaite, 2007;Harris et al, 2010;Meuthen et al, 2019). Furthermore, it is also possible that patterns of feeding (e.g., frequency or schedule) rather than diet per se could influence exploration in zebrafish (Holley et al, 2014;Le Roy et al, 2021).…”
Section: The Effect Of Obesogenic Diet On Anxietyrelated Behaviormentioning
confidence: 99%